PRELIMINARY REPORT ON ANALYSES OF MELTED DOME FUJI ICE CORE OBTAINED IN 1993 - ワタナベ, オキツグ; カミヤマ, コキチ; モトヤマ, ヒデアキ; イガラシ, マコト; マトバ, スミト; シライワ, タカユキ; ヤマダ, トモミ; ショウジ, ヒトシ; カナモリ, サトル; カナモリ, ノブコ; ナカオ, マサヨシ; アゲタ, ユタカ; et al. (National Institute of Polar Research, 1997)
P(論文) An ice core from the glacier surface down to 112.59m depth was obtained in 1993 at Dome Fuji Station. The ice core was divided vertically in the home cold laboratory and various analyses were carried out for the solid and liquid phases of core samples. The measurements of numbers of microparticles, electrical conductivity, pH, oxygen isotopic ratio and chemical constituents were carried out for the melted ice core samples. In this report, the procedures and the methods for the measurements are introduced with results obtained. The results open preliminary step on ice core research at Dome Fuji Station, which should be useful to evaluate the environments at the dome in the comparison with core analyses at various sites. The vertical distributions for the some of the values obtained are presented to facilitate further discussion of the past climate and environments. departmental bulletin paper